Transboundary impact of the lignite mining on the groundwater resources within Lusatian Neisse basin = Transgraniczne oddziaływanie górnictwa węgla brunatnego na zasoby wód podziemnych w zlewni Nysy Łużyckiej - Zdralewicz, Iwona; Adynkiewicz-Piragas, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a brief description of the lignite mines within Lusatian Neisse basin, whose activities affect the groundwater resources on both sides of the border state together with the characteristics of the kind and extent of the impact of these investments.
Keywords: kopalnie węgla brunatnego; zasoby wód podziemnych; oddziaływanie transgraniczne; zlewnia Nysy Łużyckiej; lignite mining; groundwater resources; transboundary impact